Removal of chromium from wastewater using paper waste sludge-derived hyrdrochar modified by naoh - Nguyen, Lan Huong; Van, Huu Tap; Nguyen, Quang Trung; Nguyen, Thu Huong; Nguyen, Thi Bich Lien; Pham, Thi Phuong Thuy; Le, Thai Hoang; Bui, Manh Ha; Ho, Viet The; Tilpo, Ordanza Hanna Joy; et al. (Vietnam Journal of Earth Sciences, 2020)
In this work, paper waste sludge (PWS) collected from the primary settling tank of the paper wastewater treatment plant was utilized to generate hydrochar as a low-cost adsorbent for removal of Cr(VI) from aqueous solution. The characteristics of paper waste sludge hydrochar (PWSH) and the effects of adsorption conditions of Cr(VI) onto PWSH, including solution pH (3-9), contact time (5-240 min), initial Cr(VI) concentration (10-80 mg/L) and the adsorbent dose of 1 g/L at room temperature (25±2°C) were investigated. Adsorption isotherm and kinetics were also predicted in this work. The results indicate that the maximum adsorption capacity achieved 11.89 mg/g at 120 min of contact time, pH 3, and initial Cr(VI) concentration of 60 mg/L. The adsorption isotherm was reflected the best by the Langmuir model (R2 of 0.9968). Whereas, the adsorption kinetic also indicates that the pseudo-second-order model predicted the best for Cr(VI) adsorption process with a R2 of 0.9469. The mechanism of Cr(VI) adsorption process onto PWSH was chemical sorption through electrostatic interaction and ion exchange.